Análise critica da viabilidade economica e eficiência energética de usina fotovoltaica: estudo de caso - Aragão, Carlos Eduardo Moura (Universidade Federal Rural do Semi-Árido, 2020)
Looking ahead to the growth of photovoltaic plants being adopted by the industry, it is worthy knowing the economically feasibility and how power efficient it is using data about its electricity generation and its economic strategies. A study case was made from a photovoltaic plant from a local business named AMANA, by surveying and using the Sunny Portal platform. With all the data gathered, it was noticed the financing from FNE Sol and the business’s owner to build the power plant was worthy R$ 600.300,00, with annual electricity production around 184,32 MWh, saving around R$111.592,01 a year with electricity bills and with a investment attractiveness rating of 3% a year. With all this put together, it was observed the electricity generation from the photovoltaic panels is indeed efficient, but its implementation is economically feasible, getting very close to the estimated by the manager.
Monografia
Keywords: Usina fotovoltaica; Energia solar; Eficiência energética; Viabilidade econômica; Photovoltaic plant; Solar energy; Energetic efficiency; Economic feasibility; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA